PHYSICAL AND CHEMICAL PROPERTY ANALYSIS OF CHILI PEPPERS (Capsicum frutescens) DURING OVEN DRYING AT DIFFERENT TEMPERATURES - Murni Murni; Devi Tanggasari (Protech Biosystems Journal, 2025)
Chili Peppers(Capsicum frutescens) is a local chili variety typical of Sumbawa that has a high level of spiciness and nutrient content such as vitamin C and antioxidants. However, the short shelf life is an obstacle in its utilization, so this study aims to determine the effect of temperature variations in drying using an oven on the physical characteristics (weight loss) and chemistry (moisture content, vitamin C, and antioxidant activity) of forest cayenne pepper. The method used was a one-factor Complete Random Design (RAL), namely drying temperatures (50°C, 60°C, and 70°C), each with three replicates. The results showed that weight loss increased with temperature increase, highest at 60°C, but not statistically significant (p > 0.05). Moisture content decreased in all treatments, but the difference between temperatures was not significant (p > 0.05). The vitamin C content is significantly reduced at high temperatures (p < 0.05), with a temperature of 50°C being able to maintain vitamin C best. In contrast, antioxidant activity increased as the temperature increased, and the temperature of 70°C resulted in the highest DPPH inhibition value significantly (p < 0.05). This study concludes that drying temperature affects physical and chemical parameters differently, so the selection of drying temperature should be adjusted to the purpose of processing, whether to maintain vitamin C or increase antioxidant activity.